Efektivitas Bermain Peran Untuk Pengembangan Bahasa Anak - Musi, Muhammad Akil; Winata, Widia (Universitas Negeri Makassar, 2017)
Language development is a very important stage in the lifespan of early childhood. The problem in this study is the low ability of children in the language which is characterized by several indicators of language development. The aimed of this study was to determine the effectiveness of role-playing both macro and micro to develop the language of early childhood. The research method employed was classroom action research which approach is done through quantitative analysis (percentage analysis) to calculate the number and percentage of children who achieve the development in cycle I and cycle II. Qualitative analysis (assessment analysis) is conducted to determine the progress of children achievement in the form of not yet developed (BB), developing (MB), developing as expected (BSH) and developing very well (BSB). The data collection technique is done through observation, interview, and documentation techniques. The results show that role play is very effective for developing early childhood language skills. In language learning activities through role play then the factors that must be considered is the factors of motivation and interest of early childhood.